Tourism and its impacts projected to grow substantially in Antarctica ... - De Oliveira Anderson, Rodolfo; Lee, Jasmine; Bastmeijer, Kees; Chown, Steven (Monash University, 2024)
Abstract Antarctica, a region devoted to peace and science, faces an uncertain future amid expanding tourism, which is thought to cause cumulative environmental impacts. Much focus now exists on developing a regulatory framework for Antarctic tourism, but discussions on such a framework lack quantitative projections of tourism growth and its impacts. Here, based on historical data on visitor landings, we use the shared socioeconomic pathways to project numbers of future landings and their impacts. We show that under most scenarios the numbers of landings could grow dramatically by the end of the century, with the high-emission scenarios leading to a 5-fold increase of tourist activities in Antarctica. Landing numbers could be as high as 2 million landings by 2100. Industry-led norms or country-by-country regulation is likely to be less effective for mitigating impacts than an Antarctic Treaty System agreed regulatory framework that is binding. Contents Scripts used to assess the impacts of tourism on ...